2005
DOI: 10.1161/01.cir.0000153864.24034.a6
|View full text |Cite
|
Sign up to set email alerts
|

Women Have Lower Tonic Autonomic Support of Arterial Blood Pressure and Less Effective Baroreflex Buffering Than Men

Abstract: Background-Short-term and tonic regulation of arterial blood pressure (BP) differ in premenopausal women and men of similar age. The autonomic nervous system (ANS) plays a critical role in BP regulation. Methods and Results-To

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
121
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(140 citation statements)
references
References 33 publications
15
121
1
3
Order By: Relevance
“…Indeed, there have been reports using indirect indices of sympathetic nerve activity showing that men have a predominance of sympathetic effects on the heart interval using spectral analysis, 39,40 and higher circulating catecholamine levels than women. 41 These reported findings are consistent with our results of an existing difference in the sympathetic drive between women and men.…”
Section: For Hypertensive Women (F-eht) and Men (M-eht) Normotensivesupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, there have been reports using indirect indices of sympathetic nerve activity showing that men have a predominance of sympathetic effects on the heart interval using spectral analysis, 39,40 and higher circulating catecholamine levels than women. 41 These reported findings are consistent with our results of an existing difference in the sympathetic drive between women and men.…”
Section: For Hypertensive Women (F-eht) and Men (M-eht) Normotensivesupporting
confidence: 93%
“…48 In that report, the baroreceptor reflex sensitivity controlling MSNA was found to be increased in relation to increased plasma levels of oestrogen and progesterone. 48 Although we did not examine the mechanisms underlying the observed gender-related differences, taking the above considerations together with previously published reports, 20,41,49,50 it is reasonable to raise the possibility that the lower sympathetic activity in women could be related to their greater sympatho-inhibitory baroreceptor reflexes than those in men. This normal genderrelated difference would then affect the level of the central sympathetic hyperactivity attained in women and men with hypertension.…”
Section: For Hypertensive Women (F-eht) and Men (M-eht) Normotensivementioning
confidence: 94%
“…Indeed, forearm vasoconstrictor responses to norepinephrine were observed to be blunted in young women compared with men (34,35). In agreement, recent studies (11,25,54) have suggested that young women exhibit lower tonic autonomic nervous system support of arterial BP compared with young men due to their lower basal sympathetic nerve activity and attenuated ␣-adrenergic sensitivity. Furthermore, a positive relationship between sympathetic nerve activity and total peripheral resistance has been reported in young men but not young women (9,27).…”
supporting
confidence: 76%
“…In a previous study, we compared responses to phenylephrine before and during near-complete ganglionic blockade to estimate baroreflex blood pressure function in women and men. 11 Baroreflex blood pressure buffering was less effective in healthy young women compared with healthy young men. The phenomenon could be related to a gender difference in baroreflex heart rate or MSNA regulation.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies suggest that baroreflex blood pressure buffering is less effective in women than in men. 11 The balance between baroreflex-mediated heart rate and muscle sympathetic nerve activity (MSNA) changes may also be influenced by gender. The idea is supported by the observation that resting sympathetic vasomotor tone tends to be decreased in women, 12,13 whereas resting heart rate is increased.…”
mentioning
confidence: 99%